Increased 68Ga-FAPI-04 Uptake in Schmorl Node in a Patient With Gastric Cancer. (August 2021) - Lin, Rong; Lin, Zefang; Zhang, Jiaying; Yao, Shaobo; Miao, Weibing
Abstract : Abstract: A 78-year-old man with a newly diagnosed gastric adenocarcinoma underwent 18 F-FDG and 68 Ga-FAPI-04 PET/CT before treatment. Both 18 F-FDG and 68 Ga-FAPI-04 PET/CT demonstrated intense radioactivity in the gastric cancer. However, the benign Schmorl node in the inferior endplate of the T5 vertebrae showed increased uptake of 68 Ga-FAPI-04, which was not FDG avid. Two months after radical gastrectomy of the gastric cancer (pT1aN0M0, IA), a follow-up CT showed that the Schmorl node in T5 vertebrae remained unchanged.